The Barbados-Panama conncetion revisited : commemorating migration fron Barbados to Panama 1904-1914 - Newton, Velma Barbados Museum & Historical Society, National Cultural Foundation and the Department of History and Philosophy, UNiversity of the West Indies, Cave Hill Campis
Barbadians were the largest group of labourers recruited by the Amerivan canal builders, for construction of the Panama Canal between 1904-1914.